Output channel design for collecting closely-spaced particle streams from spiral inertial separation devices - Caffiyar Mohamed Yousuff; Nor Hisham B Hamid; Ismail Hussain Kamal Basha; Eric Tatt Wei Ho (AIP Advances, 2017)
Recent advances in inertial microfluidics designs have enabled high throughput, label-free separation of cells for a variety of bioanalytical applications. Various device configurations have been proposed for binary separation with a focus on enhancing the separation distance between particle streams to improve the efficiency of separate particle collection. These configurations have not demonstrated scaling beyond 3 particle streams either because the channel width is a constraint at the collection outlets or particle streams would be too closely spaced to be collected separately. We propose a method to design collection outlets for inertial focusing and separation devices which can collect closely-spaced particle streams and easily scale to an arbitrary number of collection channels without constraining the outlet channel width, which is the usual cause of clogging or cell damage. According to our approach, collection outlets are a series of side-branching channels perpendicular to the main channel of egress. The width and length of the outlets can be chosen subject to constraints from the position of the particle streams and fluidic resistance ratio computed from fluid dynamics simulations. We show the efficacy of this approach by demonstrating a successful collection of upto 3 particle streams of 7μm, 10μm and 15μm fluorescent beads which have been focused and separated by a spiral inertial device with a separation distance of only 10μm -15μm. With a throughput of 1.8mL/min, we achieved collection efficiency exceeding 90% for each particle at the respective collection outlet. The flexibility to use wide collection channels also enabled us to fabricate the microfluidic device with an epoxy mold that was created using xurography, a low cost, and imprecise fabrication technique.